2003
DOI: 10.1111/j.1748-5827.2003.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocartilaginous embolism in 75 dogs: clinical findings and factors influencing the recovery rate

Abstract: The records of 75 dogs with fibrocartilaginous embolism of the spinal cord were evaluated retrospectively. The diagnosis was confirmed histopathologically in 21 dogs (group A) and remained suspected in 54 patients (group B). The two groups were compared. Particular emphasis was placed on the description of physiotherapy procedures, recovery rates and prognostic criteria. Results demonstrated that fibrocartilaginous embolism affected mainly middle-aged, large- or giant-breed dogs. Clinical signs were peracute i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
133
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(151 citation statements)
references
References 7 publications
14
133
4
Order By: Relevance
“…This syndrome is commonly reported in adult and elderly dogs, mainly in large and giant breeds (NEER, 1992;CAUZINILLE & KORNEGAY, 1996;GANDINI et al, 2003;TESSER et al, 2009), which suggested that predisposing factors, including aging or a fissure of the annulus fibrosus, facilitate entry of nucleus pulposus material into the vasculature (NEER, 1992;CAUZINILLE & KORNEGAY, 1996). Although, FCE cases in the horse are sporadic, all reports, including this one, are in adult horses, suggesting some similarity to the condition described in dogs.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This syndrome is commonly reported in adult and elderly dogs, mainly in large and giant breeds (NEER, 1992;CAUZINILLE & KORNEGAY, 1996;GANDINI et al, 2003;TESSER et al, 2009), which suggested that predisposing factors, including aging or a fissure of the annulus fibrosus, facilitate entry of nucleus pulposus material into the vasculature (NEER, 1992;CAUZINILLE & KORNEGAY, 1996). Although, FCE cases in the horse are sporadic, all reports, including this one, are in adult horses, suggesting some similarity to the condition described in dogs.…”
mentioning
confidence: 90%
“…It has been described in dogs (CAUZINILLE & KORNEGAY, 1996;DYCE & HOULTON, 1993;GANDINI et al, 2003;TESSER et al, 2009) and humans (UPPAL et al, 2004;ZACHARY, 2013), and rarely in horses (TAYLOR et al, 1977;FUENTEALBA et al, 1991;SEBASTIAN & GILES, 2004;WALLING et al, 2011). The pathogenesis of this syndrome remains uncertain and several theories have been proposed to explain the origin of fibrocartilaginous emboli.…”
mentioning
confidence: 99%
“…This condition has been well characterized in animals, especially dogs [78,79], but also in cats [80,81], horses [82], swine [83], and turkeys [84]. The first human condition was described in a 15-year-old male in 1961; nucleus pulposis emboli were found within the spinal cord arteries at autopsy [85].…”
Section: Causes Of Spinal Cord Infarction In Childrenmentioning
confidence: 99%
“…schemic myelopathy and ANNPE are common neurologic emergencies in dogs that have similar clinical signs [1][2][3][4][5][6][7][8][9][10] such as the hyperacute onset of nonprogressive, often markedly asymmetric spinal cord dysfunction without obvious signs of pain. 1,3,5,10 In dogs, ischemic myelopathy is most commonly associated with embolization of fibrocartilaginous material within the spinal cord vasculature that is histologically indistinguishable from nucleus pulposus (ie, fibrocartilaginous embolism) 5,6,[11][12][13] and causes sudden onset of regional ischemia resulting in necrosis of the spinal cord parenchyma.…”
mentioning
confidence: 99%
“…1,3,5,10 In dogs, ischemic myelopathy is most commonly associated with embolization of fibrocartilaginous material within the spinal cord vasculature that is histologically indistinguishable from nucleus pulposus (ie, fibrocartilaginous embolism) 5,6,[11][12][13] and causes sudden onset of regional ischemia resulting in necrosis of the spinal cord parenchyma. [4][5][6][11][12][13] In contrast,…”
mentioning
confidence: 99%